2017
DOI: 10.1111/jgs.14939
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Individual: The Interdependence of Advance Directive Completion by Older Married Adults

Abstract: OBJECTIVES:To determine how individual and spousal demographic and health factors are associated with advance directive (AD) completion by married older adults. DESIGN: Dyadic structural equation modeling using the Actor-Partner Interdependence Model. SETTING: The 2004 to 2012 waves of the Health and Retirement Study. PARTICIPANTS: Community-dwelling heterosexual married couples aged 65 and older (N = 2,243). MEASUREMENTS: Structural equation modeling with a probit link function was used to estimate associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 24 publications
(59 reference statements)
8
16
2
Order By: Relevance
“…Older adults who are single also were more likely than their married counterparts to indicate they were able to update and share their living will each year. Although this finding is counterintuitive and does not agree with the results of some other studies, it is possible that single older adults are more inclined to create an EOL life plan because they have to rely on themselves for planning for their future. Additional research is warranted to confirm this relationship.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Older adults who are single also were more likely than their married counterparts to indicate they were able to update and share their living will each year. Although this finding is counterintuitive and does not agree with the results of some other studies, it is possible that single older adults are more inclined to create an EOL life plan because they have to rely on themselves for planning for their future. Additional research is warranted to confirm this relationship.…”
Section: Discussioncontrasting
confidence: 87%
“…Although this finding is counterintuitive T A B L E 3 Summary of the multiple logistic regression analyses with the perceived importance of four older adult engagement self-care actions for planning for the End-of-Life and the desire and ability of older adults to perform these actions. and does not agree with the results of some other studies, 19,24,27 it is possible that single older adults are more inclined to create an EOL life plan because they have to rely on themselves for planning for their future. Additional research is warranted to confirm this relationship.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…As hypothesized, when the first spouse used hospice or had no ACP, the second spouse was more likely to engage in hospice or have no ACP. Results contribute to literature showing that married couples act similarly on a range of health behaviors, [11][12][13][14] and literature showing that spouses are more likely to have ACP if their partner has engaged in ACP 9,30 or their partner has died. [31][32][33][34][35] We expand on our understanding of spousal concordance related to ACP and hospice use through 2 additional findings.…”
Section: Discussionsupporting
confidence: 65%
“…Overall, interestingly, we found that our findings in community-dwelling nurses regarding predictors of ACP were quite similar to findings previously reported among institutionalized patients and patients at the EOL [30][31][32][33][34][35][36] (such as African American race, illness, a recent experience of death in close friends or family, and greater social support). [7][8][9]11,18,19,25,[37][38][39][40][41][42] Among these former nurses, although the prevalence for ACP documentation was high at 84%, the prevalence for recent ACP discussions with physicians was much lower at 35%. Yet the evidence is increasingly clear that efforts to facilitate patient-centered EOL care should focus on encouraging ongoing patient-clinician ACP discussions.…”
Section: Discussionmentioning
confidence: 99%